Implementasi Penanaman Nilai Karakter Anak di RA Raudlatul Kholafiyah - Ika Sriwahyuni (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to describe the implementation of character education for early childhood at RA Raudlatul Kholafiyah Jangkang, Tiris District, Probolinggo Regency, and to identify its supporting and inhibiting factors. Character education in early childhood is essential for shaping children’s moral, spiritual, and social development. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving the principal, teachers, students, and parents, and analyzed using Miles and Huberman’s interactive model. The results show that character values are integrated through routine, thematic, and daily habituation activities focusing on honesty, discipline, responsibility, and helpfulness. The main methods include habituation, exemplary modeling, storytelling, positive reinforcement, and religious activities. Supporting factors consist of strong leadership, parental involvement, a conducive school environment, and the community’s cooperative culture. Meanwhile, obstacles include differences in parenting styles, limited learning media, uneven teacher training, and restricted learning time. Overall, character education at RA Raudlatul Kholafiyah has been implemented effectively, though stronger collaboration between school and family is needed to sustain the internalization of character values.